PENGARUH KUALITAS PRODUK DAN IKLAN TERHADAP CITRA MEREK DAN KEPUTUSAN PEMBELIAN PRODUK KECANTIKAN MEREK POND’S PADA REMAJA DI KOTA PEKANBARU - Irwanty L Situmorang; Jushermi '; Marhadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to the influence of product quality and advertising on brand image and purchase decision Pond's brand beauty products in Adolescents in Pekanbaru. In this study consisted of four variables Product Quality(X1), Advertising (X2), brand image (Y1) and the purchase decision (Y2). The population of this research is all Youth Pond's product users in the city of Pekanbaru with a sample of 96 respondents were selected using the technique of purposive sampling method or sample conditional criteria, namely Youth aged 14-19 years old and lives in Pekanbaru. Analysis of the data in this study using Path Analysis (Path Analysis) using SPSS version 21.0. Based on hypothesis testing that has been done, the results showed that the quality product and advertisement positive and significant impact on brand image. The quality products and advertising positive and significant impact on the purchase decision. Then the brand image positive and significant impact on the purchase decision. While there is a very strong influence indirectly the quality of the products on purchase decisions through brand image or in other words the brand image is able to mediate the relationship between the quality of the products on purchasing decisions, and there is a very strong influence indirectly between advertising on purchasing decisions through brand images. Keyword: Product Quality, Advertising, Brand image and Purchase Decision